Mindful Mates: A Pilot Study of the Relational Effects of Mindfulness‐Based Stress Reduction on Participants and Their Partners. Issue 3 (26th May 2016) - Khaddouma, Alexander; Coop Gordon, Kristina; Strand, Elizabeth B.
Abstract : Very little is currently known about how increases in dispositional mindfulness through mindfulness training affect the quality of participants' romantic relationships, and no previous studies have examined how increases in specific facets of mindfulness differentially contribute to relationship health. Additionally, even less is known about how an individual's development of mindfulness skills affects the relationship satisfaction of his or her romantic partner. Thus, the purpose of this pilot study was to examine associations between changes in facets of mindfulness and relationship satisfaction among participants enrolled in a Mindfulness‐Based Stress Reduction (MBSR) course and their nonenrolled romantic partners. Twenty MBSR participants and their nonenrolled partners ( n  = 40) completed measures of mindfulness and relationship satisfaction pre‐ and post‐enrolled partners' completion of an MBSR course. Results indicated that enrolled participants significantly improved on all facets of mindfulness and relationship satisfaction, while nonenrolled partners did not significantly increase on any facet of mindfulness or relationship satisfaction. Moreover, enrolled participants' increases in Acting with Awareness were positively associated with increases in their own and their nonenrolled partners' relationship satisfaction, whereas increases in enrolled participants' Nonreactivity were positively associated with increases in their nonenrolled partners' (but not their own) relationship satisfaction. These results suggest that increasing levels of mindfulness (particularly specific aspects of mindfulness) may have positive effects on couples' relationship satisfaction and highlight mindfulness training as a promising tool for education and intervention efforts aimed at promoting relational health.